In vivo systems - Smith, Quentin (Henry Stewart Talks, 2008)
Common issues in brain uptake assessment, Multiple factors impact brain delivery and exchange, Assumptions, What information is sought?, What brain compartment is appropriate?, Brain transport kinetics, In vivo methods to assess BBB transport, In situ brain perfusion method, Systemic (IV) administration method, Brain microdialysis method, Brain efflux index (BEI) method
Archived at 2018/05/31